Analisis Biaya Sumberdaya dalam Negeri dan Kepekaannya pada Usaha Ternak Babi di Sumatera Utara - Budiman Hutabarat; Bambang Winarso (Jurnal Agro Ekonomi, 1994)
North Sumatera has exercised its comparative advantage in various forms of farm activities including pig raising undertaking. The paper aims to analyze the domestic resource costs and its sensitivity in pig farming in the province. Empirical data were obtained from six pig farming enterprises and eleven "small" pig farms closed to the location of each enterprise in Kabupaten Deli Serdang, Kotamadya Binjai, and Kotamadya Medan from March through April 1992. The research concludes that North Sumatera has comparative advantage in pig production for its domestic resource costs ratios are still below unity. The comparative advantage is even more significant in producing suckling pigs. The domestic resource costs ratios are more affected by pig prices than feed input prices, especially on weaned pigs. Between feed prices considered, corn price is more significant than concentrate price in determining the domestic resource costs ratios. Therefore, improving land productivity on corn to make it cheaper in the market especially for pig raising activities should be a continuing effort.